Investigating the Potential of Clitoria ternatea Linn. for Neuropharmacology: A Review - Anjali M. Wanegaonkar; Dhanashree Tembare; Neeta Jena; Mudranka Patil; Tushar Tagwale; Shrutika Patil (Pharmaceutical Science: New Insights and Developments Vol. 5, 2025)
Clitoria ternatea Linn (CT), a traditional Ayurvedic herb, has a longstanding history in traditional medicine. Modern studies now validate its efficacy in treating various neurodegenerative conditions, such as Alzheimer’s disease, Parkinson’s disease, and even stress-related disorders. Alzheimer’s disease (AD) is an age-related neurodegenerative disorder characterized by the irreversible loss of cognitive function, memory, and language impairment, and behavioral disturbances, which gradually become more severe. Medicinal plants are the backbone of modern medicines, and there is growing interest in discovering nootropic plants to combat cognitive dysfunction due to their less harmful effects. CT, is also known as ‘Aparjita/Butterfly pea’, has been used for centuries as a memory enhancer, antistress, anxiolytic, antidepressant, anticonvulsant, and antiulcer agent. These properties of CT raise the possibility of using it as a cholinesterase inhibitor in treating neurological disease symptoms. The preliminary phytochemical screening showed that the plant contained tannins, phlobatannin, carbohydrates, saponins, triterpenoids, phenols, flavanoids, flavonol glycosides, proteins, alkaloids, antharaquinone, anthocyanins, cardiac glycosides, Stigmast-4-ene-3, 6-dione, volatile oils and steroids. This review focused not only on available information about the neuropharmacological use of this plant but also its bioactive compounds, metabolites, and associated effects. It reviewed the existing knowledge to reveal the promising linkage of traditional medicine CT to halt Alzheimer’s disease pathogenesis. This study opens new doors for researchers with a wide range of neuropharmacological activities that could be utilized in developing suitable formulations, especially for the treatment of neurodegenerative disorders.